2016
DOI: 10.1056/nejmoa1609409
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan for the Prevention of Acute Organ Dysfunction in Sepsis

Abstract: BACKGROUNDLevosimendan is a calcium-sensitizing drug with inotropic and other properties that may improve outcomes in patients with sepsis. METHODSWe conducted a double-blind, randomized clinical trial to investigate whether levosimendan reduces the severity of organ dysfunction in adults with sepsis. Patients were randomly assigned to receive a blinded infusion of levosimendan (at a dose of 0.05 to 0.2 μg per kilogram of body weight per minute) for 24 hours or placebo in addition to standard care. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
238
2
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(255 citation statements)
references
References 33 publications
5
238
2
10
Order By: Relevance
“…According to the SSCG 2012,29 dobutamine use is recommended (Grade 1C) (i) when cardiac function is declining, and (ii) in amounts of up to 20 μg/kg/min when low perfusion persists despite adequate fluid resuscitation. However, the Japanese Clinical Practice Guidelines for the Management of Sepsis and Septic Shock (1st edition)2 states that, “As improvement of reduced cardiac function is difficult to achieve with dobutamine in septic shock, combined administration with a phosphodiesterase III inhibitor or a calcium sensitivity enhancer should be considered as an alternative.” One RCT (the LeoPARDS [Levosimendan for the Prevention of Acute oRgan Dysfunction in Sepsis] trial) to evaluate calcium sensitivity enhancers in patients with sepsis was performed recently, but no prognostic improvement effect was observed 124. It was determined that the quality of the evidence supporting the recommendation of these drugs is currently poor, and accordingly, this guideline does not include a CQ on their use.…”
Section: Introductionmentioning
confidence: 99%
“…According to the SSCG 2012,29 dobutamine use is recommended (Grade 1C) (i) when cardiac function is declining, and (ii) in amounts of up to 20 μg/kg/min when low perfusion persists despite adequate fluid resuscitation. However, the Japanese Clinical Practice Guidelines for the Management of Sepsis and Septic Shock (1st edition)2 states that, “As improvement of reduced cardiac function is difficult to achieve with dobutamine in septic shock, combined administration with a phosphodiesterase III inhibitor or a calcium sensitivity enhancer should be considered as an alternative.” One RCT (the LeoPARDS [Levosimendan for the Prevention of Acute oRgan Dysfunction in Sepsis] trial) to evaluate calcium sensitivity enhancers in patients with sepsis was performed recently, but no prognostic improvement effect was observed 124. It was determined that the quality of the evidence supporting the recommendation of these drugs is currently poor, and accordingly, this guideline does not include a CQ on their use.…”
Section: Introductionmentioning
confidence: 99%
“…Of note, the defined daily dose price of levosimendan is about 22 times higher than dobutamine 16. We recommend that if clinicians prefer to use levosimendan rather than dobutamine in this population, they do so in the context of high‐quality RCTs, given the lack of data on the balance between the benefits and harms of levosimendan in patients with acute circulatory failure in general, the suggested harm of levosimendan in patients with sepsis,25 and the higher price.…”
Section: Resultsmentioning
confidence: 99%
“…We refrain from giving any recommendations or suggestions on using dobutamine or levosimendan for patients with hypovolemic shock, due to the lack of data and no relevant populations to extrapolate from. In the recently published LEOPARDS trial in which adult patients with sepsis were randomized to levosimendan or placebo, levosimendan was associated with a lower likelihood of successful weaning from mechanical ventilation and a higher risk of supraventricular tachyarrhythmia compared to placebo 25. This cautions use of levosimendan in other patient groups, including patients with hypovolemic shock.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is evidence that levosimendan reduces mortality in patients with severe sepsis and septic shock (33). However, a large clinical trial recently showed that levosimendan does not improve organ function nor does it lower mortality in patients with sepsis (34). Further studies are necessary and large clinical trials are currently being conducted in order to investigate the role of levosimendan in the treatment of severely ill patients other than those with heart failure and those undergoing cardiac surgery where the role of this drug is already well determined.…”
Section: Calcium Sensitizersmentioning
confidence: 99%